Epididymo-Orchitis as a Presenting Feature of Relapsing Polychondritis: A Case Report - Kuljeet Bhamra; Rachel Weerasinghe; Alan Steuer (Case Reports in Rheumatology)
Relapsing polychondritis (RP) is a rare multisystem disease. It is characterized by recurrent inflammation of cartilaginous structures including the ears, nose, tracheo-bronchial tree and peripheral joints. Proteoglycan-rich structures such as the heart, eyes and blood vessels can also be affected. Systemic symptoms including fever, weight loss and lethargy are common. RP is difficult to diagnose as it presents in a wide variety of ways and there is no diagnostic test. Corticosteroids are the mainstay of treatment but other immunosuppressive drugs can be used in combination with steroids. We present an unusual presentation of RP.